EC Visa Facilitataion and Readmission Agreements: Implementing a New EU Security Approach in the Neighbourhood - Trauner, Florian; Kruse, Imke (2008)
Abstract: With the Eastern Enlargement successfully completed, the EU is searching for a proper balance between internal security and external stabilisation that is acceplable to all sides. This paper focuses on an EU foreign policy instrument that is a case in point for this struggle: EC visa facilitation and readmission agreements. By looking at the EU's strategy on visa facilitation and readmission, this paper aims to offer a first systematic analysis of the objectives, substance and political implications of these agreements as a means to implement a new EU security approach in the neighbourhood. In offering more relaxed travel conditions in exchange for the signing of an EC readmission agreement and reforming domestic justice and home affairs, the EU has found a new way to press for reforms in neighbouring countries while addressing a major source of discontent in these countries. The analysis concluded with the broader implications of these agreements and argues that even if the facili